A qualitative study exploring stakeholder perspectives on the use of biological samples for future unspecified research in Malawi - Matandika, Limbanazo (BMC Med Ethics, 2020)
BACKGROUND: There is growing interest in the collection, storage and reuse of biological samples for future research. Storage and future use of biological samples raise ethical concerns and questions about approaches that safeguard the interests of participants. The situation is further complicated in Africa where there is a general lack of governing ethical frameworks that could guide the research community on appropriate approaches for sample storage and use. Furthermore, there is limited empirical data to guide development of such frameworks. A qualitative study to address this gap was conducted with key stakeholders in Malawi to understand their experiences and perspectives regarding storage and usage of samples for future research. METHODS: This study conducted 13 in-depth interviews with ethics committee members, regulators and researchers, and five focus group discussions with community representatives and clinical trial participants in Malawi. Interviews and focus group discussions were audio-recorded, transcribed verbatim, and thematically analysed. RESULTS: On the current regulatory guidelines that governs the collection, storage and reuse of samples in Malawi, participants highlighted their different understanding of it, with some indicating that it prohibited the reuse and sharing of samples, while others believed it permitted. Views on the informed consent model used in Malawi, some stakeholders expressed that the current model limited options for sample contributors regarding future use. Researchers supported storing samples for future use in order to maximize their value and reduce research costs. However, they expressed concern over the exportation of samples highlighting that it could lead to misuse and would not support the development of research capacity within Malawi. They recommended use of broad consent or tiered consent and establishment of biobanks to address these concerns. CONCLUSIONS: Study findings highlighted the need for a review of the current regulatory guideline and the development of infrastructure to support the use of stored biological samples for future use among the research community in Malawi. At the moment, there are ethical and practical concerns arising from the collection, storage and secondary use of biological samples make it hard to reconcile scientific progress and the protection of participants.